1987
DOI: 10.1161/01.res.60.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Association of decreased myocardial beta-receptors and chronotropic response to isoproterenol and exercise in pigs following chronic dynamic exercise.

Abstract: The effects of chronic dynamic exercise on myocardial beta-adrenergic and muscarinic cholinergic receptors and chronotropic sensitivity to isoproterenol were studied in 5 Yucatan miniswine. Right atrial and left ventricular biopsies, heart rate responses to isoproterenol, and maximal exercise treadmill testing were obtained before and after 10-19 weeks of treadmill running. Radioligand studies using 125I-iodocyanopindolol (ICYP) and 3H-quinuclidinyl benzilate (QNB) were used to determine the number of beta-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 28 publications
(8 reference statements)
4
21
0
Order By: Relevance
“…For example, previous studies have indicated that longterm treadmill running of pigs results in diminished maximal heart rates during exercise and isoproterenol stimulation and a down-regulation of right atrial /3-adrenergic receptors (1). In the current studies we have extended these observations and find that, in spite of this down-regulation of p-receptors, the dose of isoproterenol yielding a 50% maximal heart rate response, the ED50, is decreased after training.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, previous studies have indicated that longterm treadmill running of pigs results in diminished maximal heart rates during exercise and isoproterenol stimulation and a down-regulation of right atrial /3-adrenergic receptors (1). In the current studies we have extended these observations and find that, in spite of this down-regulation of p-receptors, the dose of isoproterenol yielding a 50% maximal heart rate response, the ED50, is decreased after training.…”
Section: Introductionsupporting
confidence: 74%
“…After recovery from surgery animals underwent pharmacological and exercise testing to determine heart rate response, maximal work rate, and maximal oxygen consumption. Details of surgical procedures and physiological responses to exercise have been reported previously (1). When exercise and pharmacological tests were complete animals underwent 7-9 wk of treadmill running (60 min/d, 5 d/wk, 9% grade, 100 m/min) and physiological and pharmacological tests were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…/3-Adrenergic Receptor Binding Studies Figure 5 shows the results of saturation isotherm experiments; ,BAR number was decreased by 6 Adenylyl Cyclase Assays Basal (unstimulated) adenylyl cyclase activity was lower in denervated animals (control, 89±17 pmol/ mg/min; 6-OHDA, 30±12 pmol/mg/min). Adenylyl cyclase activity is therefore reported as net increase in stimulation (basal subtracted) to adjust for differ- Gpp(NH)p-stimulated adenylyl cyclase activity was diminished markedly through a wide range of Gpp-(NH)p concentrations ( Figure 7).…”
Section: Plasma Catecholamine Measurementsmentioning
confidence: 99%
“…For example, 2 hours after injecting adult mice with 6-OHDA, myocardial norepinephrine concentrations were decreased 95%; by 8 weeks, however, myocardial norepinephrine concentration returned to normal, suggesting regeneration of adrenergic nerve terminals. 3 In contrast, when 6-OHDA was given repeatedly during the first 10 days of life to newborn rats, myocardial norepinephrine depletion was substantial (85%) 15 weeks later, suggesting that chronic myocardial adrenergic denervation is possible if 6-OHDA is given when adrenergic neural pathways are still forming.4 Thus, our study had two goals: to develop a model of long-term, nonsurgical myocardial adrenergic denervation, and to define the relations between myocardial 3AR number, physiological responsiveness, and postreceptor elements resulting from myocardial adrenergic denervation.…”
mentioning
confidence: 95%
See 1 more Smart Citation